Kingdom of the Netherlands-Netherlands Selected Issues. (IMF Staff Country Reports; Country Report ;, 2003)
The Selected Issues paper of the Netherlands provides an overview of the Dutch pension system. It examines the strengths and weaknesses of the existing bargaining model, compares the Dutch wage bargaining in different periods, examines the past macroeconomic performance of the Netherlands, addresses the issues of wage dispersion and differentiation, and discusses future prospects and challenges for the bargaining model. It also estimates the potential growth in the Netherlands, using statistical detrending methods.